MATERIAL FOR TEACHING CULTURE TV ,INTERNET, PICTURE - Abdulazizov Davudbek; Yusufjonova Navbahor (Journal of new century innovations, 2023)
Abstract: This chapter is an attempt to explore how localization of ELT materials can serve as a useful tool to preserve the cultural identity of EFL learners. To this end, I first examine two dominant trends in materials development, namely globally- produced versus nationally-produced materials and address the advantages as well as disadvantages of each. I will then argue that one of the main disadvantages of using globally-produced textbooks is that they generally reflect Western culture and ideology.